Involvement of ATP-binding cassette, subfamily A polymorphism with susceptibility to coronary artery disease - ZARGAR, SEEMA (D.A. Spandidos, 2013)
Coronary artery disease (CAD) is one of the leading causes of mortality in developed countries. Adenosine triphosphate (ATP)-binding cassette A1 (ABCA1) belongs to the superfamily of membrane proteins that function as a key factor in the regulation of plasma high-density lipoprotein cholesterol (HDL-C) and the metabolism of apolipoprotein A-I (Apo AI). The role of this gene in CAD remains controversial. The aim of this study was to investigate the frequency of single-nucleotide polymorphism (SNP) rs2230806 in the ABCA1 gene of 120 CAD patients and 100 age-matched, healthy controls using restriction fragment length polymorphism and direct sequencing. Total serum cholesterol, HDL-C and serum triglyceride levels were also assayed. Low-density lipoprotein cholesterol (LDL-C) was calculated using the Friedewald formula. When compared, the G allele occurred significantly more frequently in CAD patients compared to the control subjects. The odds ratio (OR) for CAD conferred by carrying the ABCA1 G allele was 2.362 [95% confidence interval (CI) 0.9055–6.161] (P<0.08). The K variant of SNP rs2230806 in the G allele was associated with a decrease in HDL-C levels, but an increased frequency of CAD. In conclusion, the results showed that SNP rs2230806 in the ABCA1 gene is significantly associated with the incidence of CAD. Homozygosity for the G allelic variant in CAD patients may be associated with an increased risk of CAD/MI.